STRUKTUR NAFKAH RUMAH TANGGA NELAYAN DI KEPENGHULUAN BAGAN PUNAK PESISIR KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU - Hazmi Rahmayani; Viktor Amrifo; Kusai Kusai (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research was conducted in November 2015 at Bagan Punak Pesisir Village Bangko Subsdistrict Rokan Hilir District Riau Province. This study aims to analyze structure a living, contribution activity a living to the total income and the allocation of the income households fisherman in Bagan Punak Pesisir Village. Methods used in research is survey with determination of respondents were snowball sampling. The number of respondents in this research as many as 12 people the next comparises of top strata, medium strata and bottom strata. Structure a living households fishermen in Bagan Punak Pesisir Village seen on three strata the top strata, medium strata and bottom strata based on the ownership assets production, asset non production and type of occupation. Overall structure basic family needs fishermen basing water (97,16 %) and landmass (2,84 %)the main living contributed by 94,23 % against income and the rest 5,73 % coming from activity a living side. Husband contributed income largest namely 91,76 % of income and the rest of 6,70 % wife and son of 1,54 %. The allocation of income distinguished on food purpose, clothing, board, transport and communication and business capital. The proportion of the allocation of income for the purpose of food reduced due to improving social status fishermen (strata).